Characterization of Monocyte-Associated Factor V - Kappelmayer, Janos; Kunapuli, Satya P; Wyshock, Edward G; Colman, Robert W (Thrombosis and Haemostasis, 1993)
We demonstrate that in addition to possessing binding sites for intact factor V (FV), unstimulated peripheral blood monocytes also express activated factor V (FVa) on their surfaces. FVa was identified on the monocyte surface by monoclonal antibody B38 recognizing FVa light chain and by human oligoclonal antibodies H1 (to FVa light chain) and H2 (to FVa heavy chain) using immunofluorescence microscopy and flow cytometry. On Western blots, partially cleaved FV could be identified as a 220 kDa band in lysates of monocytes. In addition to surface expression of FVa, monocytes also contain intracellular FV as detected only after permeabilization by Triton X-100 by monoclonal antibody B10 directed specifically to the Cl domain not present in FVa. We sought to determine whether the presence of FV in peripheral blood monocytes is a result of de novo synthesis.Using in situ hybridization, no FV mRNA could be detected in monocytes, while in parallel control studies, factor V mRNA was detectable in Hep G2 cells and CD18 mRNA in monocytes. In addition, using reverse transcriptase and the polymerase chain reaction, no FV mRNA was detected in mononuclear cells or in U937 cells, but mRNA for factor V was present in Hep G2 cells using the same techniques. These data suggest that FV is present in human monocytes, presumably acquired by binding of plasma FV, and that the presence of this critical coagulation factor is not due to de novo synthesis.